Pengelolaan Wisata Mangrove Berbasis Partisipasi Masyarakat di Desa Marannu - F Fitrawahyudi; Muhammad Nasrum; S Sofyan (Universitas Muhammadiyah Parepare)
The general problems found in the program partners were the lack of community participation in development, the lack of community knowledge and skills in managing natural resources, the lack of comprehension of village governance and tourism managers in utilizing the potential of mangrove tourism villages, and the lack of comprehension of environmental conservation to protect mangrove forest habitats. The solution offered through the KKN-PPM program were to increase community participation through empowering rural communities, especially for women and the elderly widows who are not economically productive institutionalized through the